Measuring Public Service Quality and Attaining Customer Satisfaction in Egypt - Zaazou, Zeinab Abbas (The Arab Journal of Administration, 2025)
Purpose: There has been a consistent concern within policy and academic circles regarding the performance of public sector agencies. Empirical evidence from existing literature highlights the significance of providing a high standard of service quality to achieve elevated customer satisfaction. This study seeks to assess and gauge the quality of services delivered by the public sector in Egypt through the creation of a customer satisfaction matrix. This matrix involves comparing customers’ expectations with their perceived service experiences. Design/methodology/approach: To measure customer satisfaction levels regarding the quality of public services, a customer service matrix has been formulated. Additionally, the researchers have devised a mathematical equation to represent the method of gauging the quality of public services. The equation incorporates the following symbols: y (Evaluation index); xE.S (Efficiency of Service); xQ.S (Quality of Service); xT.S (Timing of Service); xC.T (Customer Trust); and xC.S (Customer Satisfaction). Findings: The matrix furnishes public service entities with comprehensive information and insights into customers’ perceptions of public service quality. The government could initially implement it on a small scale before scaling it up to a national level. Ultimately, the researchers devised a three-point action plan comprising ‘performance objectives, actions, and measurement.’ This comprehensive plan is applicable to both public and private organizations aspiring to elevate their service quality and attain heightened customer satisfaction. Originality/ Value and What Distinguishes this Study from Other Studies: This study as far as the researchers know is presenting an up-to-date original method for measuring customer satisfaction of public services. They developed a customer service matrix and a mathematical equation for gauging the quality of public services. The outcomes present an opportunity for professional service providers to continually enhance technical and management indicators, prioritize personnel training, and engage in ongoing professional development to improve service quality.